Torqued and anti-torqued vector fields on hyperbolic spaces - Aydin, Muhittin Evren; Mihai, Adela; Ozgur, Cihan (Univ Nis, Fac Sci Math, 2025)
In this paper, we study the existence of torqued and anti-torqued vector fields on the hyperbolic ambient space H-n. Although there are examples of proper torqued vector fields on open subsets of H-n, we prove that there is not a proper torqued vector field globally defined on H-n. Similarly, we have another non-existence result for anti-torqued vector fields as long as their conformal scalar is a non-constant function satisfying certain conditions. When the conformal scalar is constant, some examples of anti-torqued vector fields are provided.
Keywords: space form; hyperbolic space; torqued vector field; anti-torqued vector field